Cnpy1 is a candidate endoplasmic reticulum chaperone of vomeronasal type 2 GPCRs - G. V. S. Devakinandan; Abdul Rishad; Nandana Nanda; Syed Dastagir Hussain; Sishir Subedi; Adish Dani (Proceedings of the National Academy of Sciences, 2026)
Mouse vomeronasal sensory neurons are continuously generated from stem cells and differentiate to express either V1R or V2R G protein–coupled receptors (GPCRs), along with their respective Gαi2 or Gαo G-protein subunits. We previously reported that Gαo-type neurons exhibit elevated expression of endoplasmic reticulum (ER) chaperones and a distinctive hypertrophic, gyroid ER architecture, suggesting specialized proteostatic demands. Here, we identify a transcript for the mouse Canopy1 ( Cnpy1) gene that yields full-length Cnpy1 protein selectively expressed in and localized to the ER of Gαo neurons. Immunoprecipitation coupled with mass spectrometry revealed that Cnpy1 associates specifically with V2R GPCRs and multiple ER chaperones. Cnpy1 deletion resulted in mice that were deficient in Gαo neuronal activation upon exposure to vomeronasal stimuli and a marked reduction in male–male aggressive behavior. In the absence of Cnpy1, Gαo neurons develop normally till birth but undergo selective, progressive apoptosis during postnatal development. Unexpectedly, Cnpy1-null vomeronasal neurons displayed neither an obvious unfolded protein response nor defects in V2R GPCR traffic to dendritic tips, indicating that Cnpy1 is required for V2R assembly or functional maturation but dispensable for their ER export. Together, these findings identify Cnpy1 as a component of an ER chaperone complex that is essential for Gαo neuron signaling and survival.